Resveratrol ameliorates penconazole-induced cardiotoxicity by inhibition of oxidative stress and apoptosis in zebrafish larvae - Xue Jiang; Jie Wang; Jin Liu; Haiyan Zhu; Jian Hu; Xingzhen Sun; Wendi Zhou (Ecotoxicology and Environmental Safety, 2023)
Penconazole (PEN) is a typical systemic triazole fungicide with cardiac toxic effects. Resveratrol (RES) is a natural polyphenolic phytochemical with antioxidation properties. This study aimed to investigate if RES could protect against PEN-induced cardiotoxicity and to determine the underlying mechanisms. Zebrafish embryos were exposed to 0, 0.5, 1 and 2 mg/L of PEN from 4 to 96 h post fertilization (hpf) and cardiac developmental toxicity was assessed. Our results showed that PEN decreased hatching rate, survival rate, heart rate and body length, with increased malformation rate and spontaneous movement. PEN induced pericardial edema and abnormal cardiac structure in myl7:egfp transgenic zebrafish, as well as downregulation of cardiac development related genes (nkx2.5, tbx2.5, gata4, noto, and vmhc). In addition, PEN elevated oxidative stress via reactive oxygen species (ROS) accumulation and triggered cardiomyocytic apoptosis by upregulation of p53, bcl-2, bax and caspase 3. These adverse outcomes were counteracted by RES, indicating that RES ameliorated PEN-induced cardiotoxicity by inhibiting oxidative stress and apoptosis in zebrafish. Taken together, this study revealed the important role of oxidative stress in PEN-induced cardiotoxicity and identified dietary RES supplementation as a novel strategy to mitigate its toxicity.